Improving Learning Outcomes and Mathematical Critical Thinking Skill in Story Problems through Problem-Based Learning - Emi Yuliani (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
The general research objective in this research was to find out the results of learning and critical thinking in mathematics about solving story problems through problem-based learning for sixth grade in SDN 18 Pontianak. The research method used classroom action research (CAR). The subjects in this study were students of sixth grade in SDN 18 Pontianak, totaling 27 students. Pre-cycle students were only 37% or as many as 10 students, while students who have not completed 73% or as many as 17 students. In the first cycle, there were still students whose scores have not met the achievement of the test results, namely 19 students completed with a percentage of 70%. Eight have not completed with a percentage of 30%., Cycle II was 92% with a total of 25 students, and 2% has not completed with a number of students 2 Thus, students can understand the how to solve story problems through learning problem based learning.